Pengaruh Kompensasi, Lingkungan Kerja Dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan Di PT Aseli Dagadu Djokdja - Prayekti Prayekti; Alivia Ayu Sekarini (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
This study aims to determine the effect of compensation, work environment and career development on employee job satisfaction at PT AseliDagaduDjokja. To determine the effect of compensation on job satisfaction at PT AseliDagaduDjokdja. To determine the effect of the work environment on PT AseliDagaduDjokdja's job satisfaction. To find out career development towards job satisfaction of PT AseliDagaduDjokdja. To determine the effect of compensation, work environment and career development simultaneously on employee job satisfaction at PT AseliDagaduDjokdjaThe independent variable used is compensation, work environment and career development while the dependent variable used is job satisfaction. The population in this study were employees of PT AseliDagaduDjokdja, amounting to 226 employees, so samples taken with Slovin formula became 70 employees. Accidental samplin sampling technique. The method of collecting data using questionnaires. The analysis technique used is multiple linear regression with a significance level of 0.05.The results obtained by the regression equation Y = 0.436K + 0.133LK + 0.105PK + e. Compensation has a positive and significant effect on employee job satisfaction at PT AseliDagaduDjokdja with a significant value of 0,000 <α (0.05). The work environment does not have a positive and significant effect on employee job satisfaction at PT AseliDagaduDjokdja with a significance value of 0.231> α (0.05). Career development does not have a positive and significant effect on employee job satisfaction at PT AseliDagaduDjokdja with a significant value of 0.344> α (0.05). There is a simultaneous effect of compensation, work environment and career development on job satisfaction with a significant level of 0.05.